2D RESISTIVITY TIME LAPSE ANALYSIS FOR POTENTIAL ZONING SLIDE WET MUD IN PANEL 7 DEEP ORE ZONE (DOZ) - Felisitas K. Ulian; Jeffri Parrangan (Faculty of Teacher Training and Education, Musamus University, 2019)
Abstract High rainfall may disrupt mining operations due to possibility of wet mud slides, occurences. One of the area wet mud slide in the mining area of